(untitled) (Western European Journal of Medicine and Medical Science, 2025)
Aspergillosis is a spectrum of diseases caused by fungi of the genus Aspergillus, ranging from allergic reactions and chronic lung disease to fulminant invasive infections in immunocompromised hosts. The diagnosis is challenging due to nonspecific signs and imperfect diagnostic tests, and treatment is complicated by drug toxicity, interactions, and emerging resistance. This article reviews the current literature, presents typical diagnostic and analytic methods, and outlines findings, discussion, and recommendations for future research and clinical care